Farm economic analyis of walnut production - Apáti, F. (International Journal of Horticultural Science, 2014)
In this present study the returning issues and profit conditions of domestic walnut production are investigated. Our objective is to determine the fact that under what conditions our walnut production may be competitive and maintained in an economic way regarding the present economic and market situations. Our analysis was carried out by a deterministic model based on a farm-level data gathering in production enterprises. The total investment cost of an up-to-date walnut orchard is up to 3000 thousands HUF per hectare and turning to productivity is expected within 8-10th years. These orchards are able to produce a yield of 3 tons per hectare in the years of productivity in a normal year, thus in case of a medium-good selling prices a profit of 500 thousand HUF per hectare may be realized. As a result at the end of the whole lifetime of the orchard (30th year) an internal rate of return (IRR) of 10 to 12% may be calculated and the return is expected in the 20th to 22nd year, which may be considered as a very late return. Taking the 20 to 25% probability of harmful whether phenomena (frost, drought) into consideration, it may be concluded that in good years a performance reaching a yield of 4 tons per hectare is necessary in the long-run in order to achieve the profitable and sustainable production in an economic way. This is managed to reach in only the most up-todate orchards.